A relação entre jornalistas e fontes em grupos do WhatsApp voltados ao telejornalismo policial do Ceará - Cavalcante, Marcos Edson Matos (2023)
This research has as object of study the relationship between journalists and sources in WhatsApp groups focused on public security. Considering the context of popular participation in the production of cyberjournalism, the objective of this research is to understand how journalists and police, firefighters, first responders and citizens not connected to public safety interact within WhatsApp groups focused on the subject. And how the photos, videos, sounds and texts sent to the groups end up being appropriated in the newsrooms of journalistic programs specialized in public safety in the production of news in Ceará. The hypothesis of this study is that the WhatsApp instant messaging application, which appeared in the United States in 2009 and was appropriated to journalistic production routines from 2013 by the newspaper Extra, from Rio de Janeiro, is one of the main, if not the main, instrument for capturing agendas of the referred programs, with the groups destined to the exchange of information on public security, central participation in this process. The empirical material for the analysis is represented by conversations extracted from three groups focused on the theme in which the researcher was inserted after identifying himself as a journalist. The groups are analyzed through non-participant observation. The period analyzed for this research was ten days: February 14, 15, 16, 17 and 27 and 28, 2023; and March 1, 2, 3 and 6 of the same year. The period chosen was randomly chosen in the selection of material collected in the field diary. As a methodology for analyzing the proposed period, the Netnography process will be used as a non-participant observer. The choice of groups, in number of three, was made by invitation. It was also possible to follow the TV Cidade application and the dimension of use for the production of the Cidade 190 program, currently the oldest journalistic focused on public safety in Ceará. As a preliminary result, the importance of citizen journalism as a source for journalists and the interaction between them within groups that, for example, tag some press professionals in some posts, was perceived. With the application of questionnaires aimed at journalists who work in television journalism focused on the area of public security, it was possible to measure the importance that the application has in the daily life of newsrooms. And how, sometimes without realizing it, professionals go beyond their work schedule to feel informed and pass on guidelines, presenting the bias of the precariousness of work relations with the advent of some technologies.